The influence of media narratives on microplastics risk perception - Valeria Pop; Alexandru Ozunu; Dacinia Crina Petrescu; Adrian-Daniel Stan; Ruxandra Malina Petrescu-Mag (PeerJ, 2023)
Background Media are the interface between scientists and citizens, communicating and interpreting the risk message and powerfully influencing individual awareness, public debate, and, hence, people’s behavior. Pollution by microplastics (MPs), a threat to public health and terrestrial and marine ecosystems, has received research, media, and public interest. However, how MPs environmental and health risks are reflected in the media and assessed in the scientific literature does not find consensus over time. To date, few studies have examined social aspects around MPs, such as, for example, factors that influence awareness and perception of the risk of MPs. In this context, the objective of this study is twofold. First, we determined if media narratives influenced Romanians’ awareness of MPs, and second, we investigated if media narratives influenced Romanians’ perceptions of MPs health and environmental risk. Method An online survey was conducted among 417 Romanian respondents. The questionnaire had 21 questions. The questions were related to the awareness of MPs, the perceived health risk of MPs, the perceived environmental risk of MPs, the intensity of exposure to media narratives about the MPs impact on health and the environment, and the demographics. Binary logistic regression was run to identify what media narratives influenced MPs awareness and risk perception. In recent times, mass media has shaped perceptions of health and environmental risks, driven by events like COVID-19 and global climate change. Our study relies on media narratives as its foundation. Results Binary logistic regression showed that the awareness of MPs is influenced by the media narrative “Microplastics in the sea threaten fish stocks” (p = 0.001). When the frequency of exposure to this media narrative increases, the probability of reporting awareness of MPs increases. Likewise, an increase in age represents a higher probability of reporting awareness of MPs. The perceived health risk of MPs, with the highest weighting, was related to the dependent variable “Leakage of harmful chemicals from MPs affects the soil” (p = 0.014). Conclusions Media narratives about plastic and MPs pollution have increased over time, influencing the perception of this risk. The study argues the need for accurate and balanced media reporting on MPs to prevent the spread of misinformation and ensure that people clearly understand MPs risks. Furthermore, a closer examination of people’s perceptions supports the design of appropriate interventions to reduce plastic consumption, thereby decreasing the risks of MPs pollution with benefits for human health and the environment.